Preference for Safe Over Risky Options in Binge Eating - Neveu, Rémi; Fouragnan, Elsa; Barsumian, Franck; Carrier, Edouard; Lai, Massimo; Nicolas, Alain; Neveu, Dorine; Coricelli, Giorgio (Frontiers in Behavioral Neuroscience, 2016)
Background: Binge eating has been usually viewed as a preference for risky over safe appetitive rewards although this view has been drawn without manipulating stressing-inducing food cues. In healthy women, stressful cues bias behavior for safer options, raising the question of whether food cues modulate binging patients’ behaviors towards safer options. Method: A cross-sectional study was conducted with binging patients (20 bulimia nervosa (BN) and 23 binging anorexia nervosa (ANB) patients) and two control groups (22 non-binging restrictive (ANR) anorexia nervosa patients and 20 healthy participants), without any concomitant impulsive disorder. We assessed decisions under risk with a gambling task with known probabilities and decisions under uncertainty with the balloon analog risk taking task (BART) with unknown probabilities of winning, in three cued-conditions including neutral, binge food and stressful cues. Results: In the gambling task, binging patients and ANR patients adopted similar safer attitudes and coherently elicited a higher aversion to losses when primed by food as compared to neutral cues. This differential behavior was also observed in the BART in BN and ANR patients only, aligning with the behavior of healthy controls when primed with stressful cues. In ANB patients, similar safer behaviors were observed in food and neutral conditions in the BART but with a higher variability in their choices in food condition. This higher variability was associated with higher difficulties to discard irrelevant information. Conclusion: Decision making under risk and under uncertainty is not fundamentally altered in binging patients but might be disturbed by a concomitant task.